To simplify the expression \( \frac{4^0 \cdot 5^{-2}}{(-2)^{-3}} \) using the properties of integer exponents, we can start by applying the rules of exponents to each term.
-
First, evaluate \( 4^0 \): \[ 4^0 = 1 \] This simplifies the expression to \( \frac{1 \cdot 5^{-2}}{(-2)^{-3}} = \frac{5^{-2}}{(-2)^{-3}} \).
-
Rewrite \( 5^{-2} \) using the property \( a^{-n} = \frac{1}{a^n} \): \[ 5^{-2} = \frac{1}{5^2} = \frac{1}{25} \]
-
Rewrite \( (-2)^{-3} \) similarly: \[ (-2)^{-3} = \frac{1}{(-2)^3} = \frac{1}{-8} \]
-
Substitute these back into the fraction: \[ \frac{5^{-2}}{(-2)^{-3}} = \frac{\frac{1}{25}}{\frac{1}{-8}} = \frac{1}{25} \cdot \left(-8\right) \]
-
This simplifies to: \[ \frac{-8}{25} \]
Thus, the simplified expression is: \[ \frac{-8}{25} \]
The final answer is: \[ \frac{-8}{25} \]